Old-Age Exclusion: Active Ageing, Ageism and Agency - De Tavernier, Wouter (2019)
This editorial serves a double purpose. It introduces the articles and commentary comprising this thematic issue on old-age exclusion, and simultaneously aims to make a concise contribution to the discussion on the relation between agency of older people and old-age exclusion. While indeed it is clear that limitations of agency due to a lack of resources in old age or age discrimination lead to exclusion of older people, the relationship between reduced agency and exclusion is less clear in the case of internalized age norms. It ends with a plea for surveys studying older populations to pay more attention to older people’s identities and life goals, opinions and reasons for action.